Trends in Hypertensive Renal Disease with Renal Failure-Related Mortality Among Gender Ethnicity and Census Regions in the United States from 1999-2000 - Faiza Ikram (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Background: Hypertensive renal disease impacts approximately 753 million individuals worldwide each year. In the US, the age-adjusted mortality rate for hypertension-related ESRD rose from 9.7 to 43.7 per 100,000 between 1999 and 2020. This study evaluates trends in hypertensive-renal disease mortality from 1999 to 2020 in the US, focusing on disparities related to gender, race, and urbanization by examination of the Age-Adjusted Mortality Rate (AAMR) to inform targeted intervention and improve outcomes. Methods: The CDC WONDER database analyzed hypertensive renal disease with renal-failure-related mortality from 1999 to 2020, calculating mortality rates and a 95% confidence interval to assess national trends. Results: Throughout the study period, males constantly exhibited a higher Age-Adjusted Mortality Rate (AAMR) for hypertensive renal disease with renal-failure-related mortality 148.92 (95% CI: 148.37 – 149.48) than females 106.11 (95% CI: 105.73 – 106.49). African American individuals exhibited the highest overall AAMR at 286.29 (95% CI: 284.68 – 287.9), starting at 186.23 in 1999 (95% CI: 179.34 – 193.13) and increasing to 529.72 in 2020 (APC: 5.27; 95% CI: 520.77 – 538.67). From 1999 to 2020, AAMR rose in metropolitan areas from 197.57 (95% CI: 187.88–207.26) to 1112.12 (APC: 10.00; 95% CI: 1093.39–1130.85), and in non-metropolitan areas from 97.35 (95% CI: 90.63–104.08) to 643.06 (APC: 11.81; 95% CI: 627.76–658.37).AAMRs varied significantly by state, from 61.23 (95% CI: 59.29–63.16) in Connecticut to 225.06 (95% CI: 214.96–235.16) in the District of Columbia. Conclusion: From 1999 to 2020, the mortality rate from hypertensive-related renal diseases rose uncertainly. Higher deaths were observed in males, African American ethnicity, and individuals living in non-metropolitan areas. Addressing these problems requires a multifactorial public health approach focusing on early detection and targeted intervention to reduce disease burden. Keywords: Hypertensive Renal Disease; chronic kidney disease; kidney damage;